From Victims to Survivors: Understanding the victimssuffering - (:unkn) unknown (Routledge, 2024)
This chapter presents a review of the literature related to the impact of sexual abuse in human development and focuses on abuses perpetrated on children. It is divided in three sections. First, the author analyzes the short term and long-term consequenc...
Keywords: Víctimas; Supervivencia